Planets, Stars, and Galaxies - Ritter, Gordon (New York : Chelsea House, 2008)
Provides information about the universe and the things in it, discussing its size, structure, physical laws relating to it, and what other worlds might be like.
The universe (and welcome to it!) -- The mathematics of motion -- Newton, Kepler, and gravity -- Observing the night sky -- Relativity and black holes -- The large-scale structure of the universe.
Includes bibliographical references (p. 109-111) and index.
Keywords: Astrophysics; Cosmology; Universe